Ozone ProfilE Retrieval Algorithm (OPERA) for nadir-looking satellite instruments in the UV–VIS ... : خوارزمية استرجاع ملف تعريف الأوزون (أوبرا) لأدوات الأقمار الصناعية ذات المظهر الحضيض في الأشعة فوق البنفسجية ... - Jacob C. A. van Peet; Ronald van der A; O. N. E. Tuinder; Elián Wolfram; J. Salvador; P. F. Levelt; H. Kelder (OpenAlex, 2014)
Abstract. For the retrieval of the vertical distribution of ozone in the atmosphere the Ozone ProfilE Retrieval Algorithm (OPERA) has been further developed. The new version (1.26) of OPERA is capable of retrieving ozone profiles from UV–VIS observations of most nadir-looking satellite instruments like GOME, SCIAMACHY, OMI and GOME-2. The setup of OPERA is described and results are presented for GOME and GOME-2 observations. The retrieved ozone profiles are globally compared to ozone sondes for the years 1997 and 2008. Relative differences between GOME/GOME-2 and ozone sondes are within the limits as specified by the user requirements from the Climate Change Initiative (CCI) programme of ESA (20% in the troposphere, 15% in the stratosphere). To demonstrate the performance of the algorithm under extreme circumstances, the 2009 Antarctic ozone hole season was investigated in more detail using GOME-2 ozone profiles and lidar data, which showed an unusual persistence of the vortex over the Río Gallegos observing ... : الخلاصة: من أجل استرجاع التوزيع الرأسي للأوزون في الغلاف الجوي، تم تطوير خوارزمية استرجاع ملف تعريف الأوزون (OPERA). الإصدار الجديد (1.26) من OPERA قادر على استرداد ملفات تعريف الأوزون من ملاحظات UV - Vis لمعظم أدوات الأقمار الصناعية ذات المظهر الحضيض مثل GOME و SCIAMACHY و OMI و GOME -2. يتم وصف إعداد OPERA وتقديم النتائج لملاحظات GOME و GOME -2. تتم مقارنة ملفات تعريف الأوزون المسترجعة على مستوى العالم مع مسابير الأوزون لعامي 1997 و 2008. تقع الاختلافات النسبية بين GOME/GOME -2 ومسابير الأوزون ضمن الحدود التي تحددها متطلبات المستخدم من برنامج مبادرة تغير المناخ (CCI) التابع لوكالة الفضاء الأوروبية (20 ٪ في التروبوسفير، و 15 ٪ في الستراتوسفير). لإثبات أداء الخوارزمية في ظل الظروف القصوى، تم التحقيق في موسم ثقب الأوزون في أنتاركتيكا لعام 2009 بمزيد من التفصيل باستخدام ملفات تعريف الأوزون GOME -2 وبيانات ليدار، والتي أظهرت استمرارًا غير عادي للدوامة فوق محطة مراقبة ريو غاليغوس (51درجة جنوبًا، 69.3درجة غربًا). من خلال تطبيق أوبرا على أدوات متعددة، يمكن إنشاء سلسلة زمنية من ملفات تعريف الأوزون من 1996 إلى 2013 ...